Diabetes Curriculum for Pediatric Endocrine Fellowship Utilizing Modified Team-Based Learning - Ioanna Athanassaki; Sarah Lyons; Daniel DeSalvo; Kristen Hendrix; Sophia Ebenezer; Bonnie McCann-Crosby; Maria Redondo; Min-Jye Chen; Serife Uysal; Stephanie Sisley (Association of American Medical Colleges, 2020)
Introduction While type 1 diabetes is frequently encountered clinically in pediatric endocrinology fellowship training, other types of diabetes may only be encountered in educational settings. Adult learners learn best through knowledge application, but to date there are no published curricula utilizing application educational strategies for all forms of diabetes. Methods We utilized a team-based learning (TBL) approach to create four modules on different types of diabetes: type 1 diabetes, type 2 diabetes, neonatal diabetes, and maturity-onset diabetes of the young. We divided our fellows (all training years, n = 11) into two teams and delivered four separate, 90-minute sessions. To emphasize the application of knowledge, we modified the format to combine the readiness assurance test (RAT) with application problem (APP) questions. The combined RAT/APP questions were answered by individuals and teams. We analyzed scores from individual and team tests and evaluated each module. Additionally, we acquired subjective data from the fellows regarding their experiences. Results Teams outperformed individuals on the tests, as expected (94% vs. 76% correct questions, respectively). All the fellows agreed that the sessions should be included permanently. Additionally, all agreed the sessions helped them apply knowledge. Subjectively, the fellows were very engaged and lively during the sessions and felt the sessions were feasible as implemented. Discussion TBL can be a valuable educational strategy to increase the application of knowledge for diabetes in pediatric endocrinology fellows. Future studies examining the use of this strategy to increase critical thinking skills and knowledge retention in the long-term would be useful.